Pac-12 CARE-Affiliated Program: structure, methods and initial results - Kimberly G Harmon; Sourav K Poddar; Adam D Bohr; Matthew B McQueen; Jamshid Ghajar; Doug F Aukerman; Russell Romano; Theresa D Hernández; Niki Konstantinides; David J Petron; Christopher Giza (BMJ Open Sport & Exercise Medicine)
Sport-related concussion has garnered increasing scientific attention and research over the last decade. Collegiate student-athletes represent an important cohort in this field. As such, the Pac-12 CARE-Affiliated Program (CAP) was formed in 2017 as a regional hub of the Concussion Assessment, Research and Education (CARE) consortium. CAP is multisite, prospective, longitudinal study that aims to improve student-athlete health by identifying factors associated with concussion incidence and recovery and using this knowledge to inform best clinical practices and policy decisions. CAP employed a staggered rollout across the Pac-12, with the first four institutions enrolling in fall 2018. After receiving institutional review board (IRB) approval, these institutions began consenting student-athletes to share clinical concussion and baseline data for research purposes. Athletes completed baseline testing that included a medical questionnaire, concussion history and a battery for clinical concussion assessments. Concussed student-athletes were given the same battery of assessments in addition to full injury and return to play reports. Clinicians at each university worked with a data coordinator to ensure appropriate reporting, and the Pac-12 Concussion Coordinating Unit at the University of Colorado Boulder provided oversight for quality control of the data study wide. During year 1, CAP consented 2181 student-athletes and tracked 140 concussions. All research was conducted with the appropriate IRB approval across the participating Pac-12 institutions. Data security and dissemination are managed by the Presagia Sports Athlete Electronic Health Record software (Montreal, Quebec, Canada) and QuesGen Systems (San Francisco, California, USA).